Studying the Impact of Soil Stabilization Techniques on Rigid Pavement Joints Across Various Axle Loads - Thamir Ibraheem, Asma; M. Alddin, Hassan M. Mahdi (Al-Nahrain Journal for Engineering Sciences, 2024)
Rigid pavement slabs are erected on a prepared subgrade or foundation layer, providing a hard and continuous surface. Transverse joints made of dowel bars connect them, and longitudinal joints made of tie bars join them longitudinally. This study is an investigation of the impact of soil strength and concrete parameters on the effectiveness of dowel bars in rigid pavements. Moreover, three parameters were examined; California Bearing Ratio (CBR), concrete compressive strength and slab thickness. The analysis was conducted using the Ever FE program and focused on several axle configurations applied to the joint. The results indicate inverse association between the pavement slab thickness and the concrete strength, under the assumption of consistent soil strength. Moreover, an assortment of reduced shear forces on the dowel bars is seen when the soil strength values increase. It indicates that soil strength has a greater impact on the shear load of dowel bars compared to the qualities of concrete. Additionally, the type of axles used and the magnitude of soil strength were shown to have a significant effect on the shear load.